From Garden to Medicine: Exploring the Ethnobotany, Phytochemistry, and Bioactivities of Mussaenda erythrophylla - N.S. Disha,; B.S. Ashok Kumar, (The Bioscan, 2025)
Musenda Erythrophila Shumach. & Thonn. (Rubiyasi), commonly known as a red flag bush, is a tropical medicinal plant in West Africa with significant dynastic significance. Traditionally used to treat wounds, fever and inflammatory disorders, its therapeutic capacity are attributed to bioactive compounds including flavonoids (quercetin, campperol), tannins, and terpenoids. Scientific studies are Staphylococcus aureus (MIC = 0.5 mg/ml), antioxidant capacity (in IC 50 = 12.4 μg/mL DPPH perfect), and COX -2 obstruction (δg = δ.2 kcal/mol) and its immunological anti -inflammatory activities. The plant also exhibits wound-medical, analgesic and antidicibitic properties, although clinical evidence is rare. Phytochemical analysis reveals diverse secondary metabolites, yet extracts and comprehensive toxicity lacks standardization of profiles. While molecular docking study predicts interactions like medicines, experimental verification through vivo models and clinical trials is mandatory. This reviews highlight the medicinal capacity of the plant, identify research intervals (mechanical studies, formulation development), and advocate permanent farming to support its integration in modern medicine. M.D. from addressing these challenges. Erythropilla may find a position as a candidate for antimicrobial, anti-inflammatory and wound-care.